The determination of the optical band and optical constants of non-crystalline and crystalline ZnO thin films deposited by spray pyrolysis - Yakuphanoğlu, Fahrettin; Ilican, S.; Caglar, M.; Caglar, Y. (Natl Inst Optoelectronics, 2007)
The optical constants and optical band gaps of the non-crystalline and crystalline zinc oxide (ZnO) thin films deposited by the spray pyrolysis method onto glass substrates at the different deposition times have been investigated by optical characterization method. The structure of the films was analyzed by X-ray diffraction and the results obtained showed that the film structure changed from non-crystalline to crystalline with increasing the deposition time. The effect of film thickness on the bandgap and optical constants (refractive index, extinction coefficient and dielectric constants) of these films has been investigated and the film thickness changes the optical constants and Urbach energy values of the films. The direct band gaps E-gi of S1, S2, S3 and S4 thin films were determined 3.295 eV 3.280 eV, 3.297 eV and 3.295 eV, respectively. It can be evaluated that the film thickness does almost not change the optical band gap of the films. The width of the tails of localized states in the optical band gap of the films increases with increasing non crystalline film thickness. The dispersion curves of the refractive index of the non crystalline films obey single-oscillator model, whereas the curves of the crystalline films do not obey this model. The dispersion parameters such as E-o. (single-oscillator energy) and E-d (dispersive energy) of the non crystalline films were determined. These values increase with increasing film thickness.
Keywords: non-crystalline films; zinc oxide; spray pyrolysis; X-ray diffraction; optical properties